Substrate-biased activity-based probes identify proteases that cleave receptor CDCP1 - Kryza, Thomas; Khan, Tashbib; Lovell, Scott; Harrington, Brittney S.; Yin, Julia; Porazinski, Sean; Pajic, Marina; Koistinen, Hannu; Rantala, Juha K.; Dreyer, Tobias; Magdolen, Viktor; Reuning, Ute; et al. (Nature chemical biology, 2021)
CUB domain-containing protein 1 (CDCP1) is an oncogenic orphan transmembrane receptor and a promising target for the detection and treatment of cancer. Extracellular proteolysis of CDCP1 by poorly defined mechanisms induces pro-metastatic signaling. We describe a new approach for the rapid identification of proteases responsible for key proteolytic events using a substrate-biased activity-based probe (sbABP) that incorporates a substrate cleavage motif grafted onto a peptidyl diphenyl phosphonate warhead for specific target protease capture, isolation and identification. Using a CDCP1-biased probe, we identify urokinase (uPA) as the master regulator of CDCP1 proteolysis, which acts both by directly cleaving CDCP1 and by activating CDCP1-cleaving plasmin. We show that coexpression of uPA and CDCP1 is strongly predictive of poor disease outcome across multiple cancers and demonstrate that uPA-mediated CDCP1 proteolysis promotes metastasis in disease-relevant preclinical in vivo models. These results highlight CDCP1 cleavage as a potential target to disrupt cancer and establish sbABP technology as a new approach to identify disease-relevant proteases. A substrate-biased activity-based probe technology was developed to enable relatively facile identification of proteases responsible for specific proteolytic events in complex biological milieu, revealing that urokinase regulates CDCP1 proteolysis.